Panopticisms: from fantasy to metaphor to reality. Issue 1 (2nd January 2017) - Fludernik, Monika
ABSTRACT: Since Foucault's popularisation of Bentham's panopticon in Discipline and Punish, panopticism has become a master trope in literary criticism and inspired novelists to adopt panoptic scenarios in their work. This article follows the trajectory of the panopticon metaphor in criticism and fiction and demonstrates how the merely metaphoric model has become a reality in current penal contexts. In particular, it will be shown how literary criticism and fiction reinterpret the original Benthamite and Foucauldian constellations of the panoptic for their own purposes and that present-day penal and non-penal surveillance contradicts the rationale under which the panopticon operated for Jeremy Bentham.